Flame-retardant modified glass fiber as well as preparation method and application thereof
By combining DOPO derivatives with amino silane coupling agents to cover the surface of glass fibers, the problem of flammability of traditional glass fibers at high temperatures is solved, and the flame retardant and mechanical properties are achieved is achieved, which significantly improves the fire of the material. Safety and durability.
Patent Information
- Application Number
- CN202411372688.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-03
AI Technical Summary
Traditional glass fibers are prone to trigger the 'candle wick effect' in high temperature environments, causing the material to accelerate combustion under the action of fire sources and increase fire risk. Moreover, its flame retardant performance is limited, making it difficult to take into account both mechanical properties and flame retardant properties.
By grafting the DOPO derivative onto the glass fiber, the glass fiber is modified with an amino silane coupling agent, the flame retardant is coated to form a protective carbon layer to inhibit flame propagation, and after the amino acid treatment is treated with DOPO -PH bonding ensures the stability and flame retardant properties of the material at high temperatures.
It significantly improves the flame retardant and mechanical properties of glass fibers, suppresses the 'wick effect', exhibits lower combustion rates and better charring properties under flame contact, and enhances the safety and durability of the material.
Smart Images

Figure CN119241091A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glass fiber modification, and in particular to a flame retardant modified glass fiber and a preparation method and application thereof. Background Art
[0002] With the development of modern industry, the requirements for material performance are increasing, especially in flame retardant technology. More and more application scenarios require composite materials with excellent flame retardant properties. Traditional glass fibers are widely used in reinforced plastics, building materials, and electrical insulation materials due to their excellent mechanical properties and chemical stability. However, the flame retardant properties of ordinary glass fibers are limited, especially in high temperature environments, which may cause a "wick effect", causing the material to burn faster under the action of a fire source, thereby increasing the risk of fire. Therefore, the development of a modified glass fiber with good flame retardant properties has become an important issue that needs to be urgently addressed in the current field of materials science.
[0003] In this context, the introduction of DOPO derivatives provides a new idea for the flame retardant modification of glass fibers. DOPO derivatives are a class of compounds with excellent flame retardant properties, and their molecular structure contains functional groups that can effectively inhibit combustion. By grafting DOPO derivatives onto glass fibers, their surface properties and flame retardant properties can be significantly improved. This method can not only enhance the stability of glass fibers in high temperature environments, but also form a protective carbon layer during combustion, thereby effectively preventing the spread of flames. At the same time, the application of grafting technology can also ensure that the mechanical properties of the modified glass fibers are not significantly affected, maintaining their excellent reinforcement effect.
[0004] In addition, applying this flame-retardant modified glass fiber to nylon materials can effectively solve the "wick effect" of traditional nylon reinforced materials. As a synthetic material widely used in textiles, automobiles, electronics and other fields, nylon is often limited in its performance under high temperature and flame environments. By introducing flame-retardant modified glass fiber, not only can the flame retardant grade of nylon materials be improved, but also its thermal stability and mechanical properties can be enhanced. Studies have shown that the modified nylon material exhibits a lower burning rate and better carbonization characteristics under flame contact, thus providing a guarantee for safety and durability in practical applications. This new type of composite material has broad market prospects and provides innovative solutions for various industries that require high-performance flame-retardant materials. Summary of the invention
[0005] The present invention aims to provide a flame retardant modified glass fiber and a preparation method and application thereof, which can suppress the "wick effect" of the material while ensuring the mechanical properties of the material.
[0006] To achieve the above object, the present invention adopts the following technical scheme: a flame retardant modified glass fiber, which is modified by an amino silane coupling agent and then coated with the flame retardant on the surface of the glass fiber.
[0007] Preferably, as an improvement, the amino silane coupling agent is at least one of 3-aminopropyltriethoxysilane (KH550), 3-aminopropyltrimethoxysilane (APS), N(2-aminoethyl)3-aminopropylmethoxysilane (AAPS), and N(2-aminoethyl)3-propylaminomethoxymethylsilane (AEAPS).
[0008] Preferably, as an improvement, the flame retardant is DOPO-PH, and the added amount of DOPO-PH is 1%-10% of the mass of the amino-modified glass fiber.
[0009] Preferably, as an improvement, the preparation method of DOPO-PH comprises the following steps:
[0010] S1, mixing 4-aminophenol, 4-hydroxybenzaldehyde and methanol, and stirring to obtain system I;
[0011] S2, adding methanol to system I and cooling in an ice-water bath to precipitate the product 2-[(phenylimino)methyl]phenol, filtering and separating the solid and washing with cold methanol;
[0012] S3, dissolving 2-[(phenylimino)methyl]phenol and DOPO in tetrahydrofuran (THF), heating and stirring the mixture to obtain System II;
[0013] S4. The white precipitate in system II was filtered and washed with cold THF, and then dried under vacuum to obtain white powder DOPO-PH.
[0014] Preferably, as an improvement, in step S1, the molar ratio of 4-aminophenol to 4-hydroxybenzaldehyde is 1:1-3; the stirring temperature is 50° C., and the stirring time is 5 h.
[0015] In this technical solution, the molar ratio of 4-aminophenol to 4-hydroxybenzaldehyde has a key influence on the effectiveness of the coupling agent. Research results show that if the ratio exceeds this range, the silane coupling agent will not be fully adsorbed on the surface of the glass fiber.
[0016] Preferably, as an improvement, in step S3, the molar ratio of 2-[(phenylimino)methyl]phenol to DOPO is 0.1-1:1; the dissolution process is completed in a nitrogen atmosphere at room temperature; the mixture is heated to 60° C. and stirred for 12 h.
[0017] In the present technical solution, the molar ratio of 2-[(phenylimino)methyl]phenol to DOPO has a key influence on the effectiveness of the flame retardant. If the ratio is beyond this range, the flame retardant will not be fully adsorbed on the surface of the glass fiber.
[0018] Preferably, as an improvement, a method for preparing a flame retardant modified glass fiber comprises the following steps:
[0019] Step 1: Amino modification of glass fiber: Use amino silane coupling agent to modify glass fiber to obtain GF-NH 2 ;
[0020] Step 2, preparation of DOPO-PH;
[0021] Step 3: Synthesis of GF@DOPO-PH: 2 Disperse in a solvent to obtain a mixed solution, dissolve DOPO-PH in the solvent, and add it to the mixed solution to obtain GF@DOPO-PH.
[0022] Preferably, as an improvement, in step 1, the amount of amino silane coupling agent added is 1 wt%, the modification reaction temperature is 60-100° C., and the reaction time is 1-2 min.
[0023] Preferably, as an improvement, in step three, the solvent is at least one of ethanol, water, DMF, DMSO, and acetonitrile.
[0024] The principle and advantages of this solution are: in actual application, in this technical solution, in view of the problem that the "wick effect" and mechanical properties of glass fibers cannot be taken into account when used in composite materials in the prior art, the present invention modifies the surface of glass fibers and applies DOPO-PH flame retardant to the modification of glass fibers for the first time. DOPO-PH can self-crosslink to form carbon at a relatively low temperature and pyrolyze small molecules of polymer materials at high temperature to form a carbon layer with high thermal stability, so that the "wick effect" of the modified glass fiber material of this technical solution is well suppressed, and the flame retardant and mechanical properties of the material can be further enhanced, achieving a balance of the three, and having outstanding economic effects and important significance in the industry. In the technical research and development stage, the structural design of the flame-retardant modified glass fiber is one of the difficulties of this technical solution. It is necessary to tightly graft the flame retardant to the surface of the glass fiber while suppressing the "wick effect". In addition, the conventional glass fiber modification in the field is to perform an amination treatment on the glass fiber, and the method adopted in this solution is to graft DOPO-PH to the surface of the amination glass fiber for the first time, overcoming the technical prejudice in the field. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 These are SEM images of the glass fibers of Example 2 and Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0026] The following is further described in detail through specific implementations, but the implementation of the present invention is not limited thereto. Unless otherwise specified, the technical means used in the following implementations are conventional means well known to those skilled in the art; the experimental methods used are all conventional methods; the materials, reagents, etc. used can all be obtained from commercial channels.
[0027] Program Overview:
[0028] The invention discloses a flame retardant modified glass fiber. The glass fiber is used as a raw material, modified by an amino silane coupling agent, and then the flame retardant is coated on the surface of the glass fiber.
[0029] A method for preparing flame retardant modified glass fiber comprises the following steps:
[0030] Step 1: GF-NH 2 Synthesis: 100 g of GF (glass fiber) was dispersed in ethanol / water (500 ml, the mass ratio of ethanol to water was 450:50), and 1 wt% of an amino coupling agent (at least one of 3-aminopropyltriethoxysilane (KH550), 3-aminopropyltrimethoxysilane (APS), N (2-aminoethyl) 3-aminopropylmethoxysilane (AAPS), and N (2-aminoethyl) 3-propylaminomethoxymethylsilane (AEAPS)) was added under high-speed stirring, and the reaction was carried out at 60-100° C. for 1-2 min. After the reaction was completed, the amino glass fiber GF-NH was obtained by filtering, washing, and drying at 80° C. 2 , and its structural formula is as shown in formula (I).
[0031]
[0032] Step 2, preparation of DOPO-PH: 4-aminophenol (10.9 g, 0.1 mole), 4-hydroxybenzaldehyde (12.2 g, 0.1 mole) and methanol were placed in a three-necked round-bottom flask equipped with a magnetic stirrer. The resulting mixture was stirred at 50°C for 5 h under a nitrogen atmosphere. The product 2-[(phenylimino)methyl]phenol was precipitated by adding methanol (200 ml) and cooling the resulting solution with an ice-water bath, and then the solid was separated by filtration and washed with cold methanol. Then, 2-[(phenylimino)methyl]phenol (10 g, 0.05 mole) and DOPO (21.6 g, 0.1 mole) were dissolved in THF (100 ml) at room temperature under a nitrogen atmosphere. The mixture was heated to 60°C and stirred for 12 h. The resulting white precipitate was filtered and washed several times with cold THF, and then dried under vacuum. The white powder was marked as DOPO-PH, and the structural formula of DOPO-PH is as shown in Formula (II).
[0033]
[0034] Step 3: Synthesis of GF@DOPO-PH: 2 Disperse evenly in ethanol (500 ml, ethanol to water mass ratio is 450:50), and dissolve the DOPO-PH prepared in step 2 in 100 ml ethanol and slowly drip into the above solution, wherein DOPO-PH / GF-NH 2 =1%-10%, after the dropwise addition is completed, the reaction is continued for 1-10 minutes. After the reaction is completed, the mixture is filtered, washed, and dried at 80°C to obtain the flame retardant modified glass fiber GF@DOPO-PH, as shown in formula (III).
[0035]
[0036] The embodiments and comparative examples of the present technical solution are shown in Table 1. The difference between the embodiments and comparative examples lies in the composition of the composite material, wherein “ / ” means no addition.
[0037] Table 1
[0038] Raw material components Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 PA6(Nylon 6) 70 70 70 70 70 70 100 <![CDATA[GF-NH 2 ]]> / / / 27 25 22 / DOPO-PH / / / 3 5 8 / GF@3%DOPO-PH 30 / / / / / / GF@5%DOPO-PH / 30 / / / / / GF@8%DOPO-PH / / 30 / / / /
[0039] Note: GF@3%DOPO-PH in Table 1 means that when flame retardant modified glass fiber is used, the addition amount of flame retardant DOPO-PH is 3%.
[0040] Taking Example 1 as an example, a method for preparing a flame retardant modified glass fiber reinforced composite material is described in detail, comprising the following steps:
[0041] Step 1: GF-NH 2 Synthesis: 100 g of GF (glass fiber) was dispersed in ethanol / water (500 ml, the mass ratio of ethanol to water was 450:50), and 1 wt% of an amino coupling agent (3-aminopropyltriethoxysilane (KH550)) was added under high-speed stirring, and the reaction was carried out at 80°C for 1 min. After the reaction was completed, the amino glass fiber GF-NH was obtained by filtering, washing, and drying at 80°C. 2 .
[0042] Step 2, preparation of DOPO-PH: 4-aminophenol (10.9 g, 0.1 mole), 4-hydroxybenzaldehyde (12.2 g, 0.1 mole) and methanol were placed in a three-necked round-bottom flask equipped with a magnetic stirrer. The resulting mixture was stirred at 50°C for 5 h under a nitrogen atmosphere. The product 2-[(phenylimino)methyl]phenol was precipitated by adding methanol (200 ml) and cooling the resulting solution with an ice-water bath, and then the solid was separated by filtration and washed with cold methanol. Then, 2-[(phenylimino)methyl]phenol (10 g, 0.05 mole) and DOPO (21.6 g, 0.1 mole) were dissolved in THF (100 ml) at room temperature under a nitrogen atmosphere. The mixture was heated to 60°C and stirred for 12 h. The resulting white precipitate was filtered and washed with cold THF three times, then dried under vacuum, and the white powder was labeled as DOPO-PH.
[0043] Step 3: Synthesis of GF@DOPO-PH: 2 Disperse evenly in ethanol (500 ml, ethanol to water mass ratio is 450:50), and dissolve the DOPO-PH prepared in step 2 in 100 ml ethanol and slowly drip into the above solution, wherein DOPO-PH / GF-NH 2 =3%, after the dropwise addition is completed, the reaction is continued for 1-10 min. After the reaction is completed, the mixture is filtered, washed, and dried at 80° C. to obtain the flame retardant modified glass fiber GF@DOPO-PH.
[0044] Preparation of GF@DOPO-PH reinforced composite material: 70g of PA6 and 30g of GF@3%DOPO-PH were dried and mixed evenly in a high mixer, and then melted and extruded into granules using a screw extruder. The granules were dried at 80°C for 12h and then injection molded using an injection molding machine to obtain test samples. The temperatures of each section of the extruder were 230±10, 240±10, 255±10, 250±10, 245, 245°C, and the main screw speed was 25±1HZ; the temperatures of each section of the injection molding machine were 250±10, 245±10, 240±10, 230±10, and flame-retardant and compatibilized glass fiber reinforced nylon 6 composite materials were obtained.
[0045] Experimental Example 1 SEM Scanning
[0046] The flame retardant modified glass fibers prepared in the above-mentioned Example 2 and Comparative Example 2 were observed by scanning electron microscope. The test results are as follows: Figure 1 shown.
[0047] Experimental Example 2
[0048] The mechanical properties and flame retardant properties of the composite materials prepared in the above embodiments and comparative examples were tested. The flame retardant property test method was carried out with reference to GB / T 2408-2008 and ASTM D2863; the mechanical property test method was carried out with reference to GB / T1040.1-2018 and GB / T 1843-2008, and the test results are shown in Table 2. From the data in Table 2, it can be seen that the flame retardant properties of the flame retardant reinforced composite materials in the embodiments of the present invention are significantly better than those in the comparative examples. From the mechanical property test results, it can be seen that the flame retardant modified composite materials prepared by the present technical solution can not only ensure flame retardancy, but also take into account the mechanical properties of the materials. The tensile strength and notched impact strength are better than those of the comparative experimental group.
[0049] Table 2
[0050]
[0051] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.
Claims
1. A flame retardant modified glass fiber, characterized in that: After the glass fiber is modified by using an amino silane coupling agent, the flame retardant is coated on the surface of the glass fiber.
2. The flame retardant modified glass fiber according to claim 2, characterized in that: The amino silane coupling agent is at least one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, N(2-aminoethyl)3-aminopropylmethoxysilane and N(2-aminoethyl)3-propylaminomethoxymethylsilane.
3. The flame retardant modified glass fiber according to claim 3, characterized in that: The flame retardant is DOPO-PH, and the added amount of DOPO-PH is 1%-10% of the mass of the amino-modified glass fiber.
4. The flame retardant modified glass fiber according to claim 4, characterized in that: The preparation method of DOPO-PH comprises the following steps: S1, mixing 4-aminophenol, 4-hydroxybenzaldehyde and methanol, and stirring to obtain system I; S2, adding methanol to system I and cooling in an ice-water bath to precipitate the product 2-[(phenylimino)methyl]phenol, filtering and separating the solid and washing with cold methanol; S3, dissolving 2-[(phenylimino)methyl]phenol and DOPO in tetrahydrofuran, heating and stirring the mixture to obtain System II; S4. The white precipitate in system II was filtered and washed with cold THF, and then dried under vacuum to obtain white powder DOPO-PH.
5. The flame retardant modified glass fiber according to claim 5, characterized in that: In step S1, the molar ratio of 4-aminophenol to 4-hydroxybenzaldehyde is 1:1-3; the stirring temperature is 50° C., and the stirring time is 5 h.
6. The flame retardant modified glass fiber according to claim 6, characterized in that: In step S3, the molar ratio of 2-[(phenylimino)methyl]phenol to DOPO is 0.1-1:1; the dissolution process is completed under nitrogen atmosphere and room temperature; the mixture is heated at 60° C. and stirred for 12 h.
7. A method for preparing a flame retardant modified glass fiber according to any one of claims 1 to 6, characterized in that: The steps include: Step 1: Amino modification of glass fiber: using an amino silane coupling agent to modify the glass fiber to obtain GF-NH2; Step 2, preparation of DOPO-PH; Step 3, synthesis of GF@DOPO-PH: GF-NH2 is dispersed in a solvent to obtain a mixed solution, DOPO-PH is dissolved in the solvent, and added to the mixed solution to obtain GF@DOPO-PH.
8. The method for preparing a flame retardant modified glass fiber according to claim 7, characterized in that: In step 1, the amount of amino silane coupling agent added is 1 wt%, the modification reaction temperature is 60-100° C., and the reaction time is 1-2 min.
9. The method for preparing a flame retardant modified glass fiber according to claim 8, characterized in that: In step 3, the solvent is at least one of ethanol, water, DMF, DMSO, and acetonitrile.
Citation Information
Cited By
Flame-retardant glass fiber, preparation method thereof and fiber-reinforced thermoplastic composite material
CN120904535A
Flame retardant glass fibers, methods of making the same, and fiber reinforced thermoplastic composites
CN120904535B
Laser marking PET material and preparation method thereof
CN120988438A
